Evaluating a train-the-trainer approach for implementing obstetric life support in diverse healthcare contexts throughout Arizona: a mixed methods protocol - Shayna D. Cunningham; Rogie Royce Carandang; Laurie S. Wood; Marcia Barry; Peggy Baker; Makayla Murphy; Cheryl K. Roth; Les R. Becker; Brook Thomson; Vincent Mosesso; Jacqueline Vidosh; John Phelps; et al. (BMC Health Services Research)
Abstract Background Most medical responders are not adequately trained to recognize and treat maternal medical emergencies, including maternal cardiac arrest, and national credentialing standards do not exist. Obstetric Life Support (OBLS) is a validated simulation-based curriculum designed to equip prehospital and hospital-based healthcare workers (HCWs) with the knowledge and skills necessary to prevent, recognize, and manage maternal medical emergencies. Widespread implementation of OBLS could enhance patient safety and reduce disparities in maternal morbidity and mortality. However, research is needed to develop strategies that ensure sustained and equitable access for HCWs across diverse healthcare settings. This paper presents a protocol for evaluating a train-the-trainer approach to implement OBLS in hospitals, freestanding birthing centers, and prehospital contexts across Arizona. Methods This multisite, mixed-methods study is being conducted in collaboration with the Arizona Perinatal Trust, a regional perinatal health system that encompasses 38 in-hospital birthing centers and Level I-IV hospitals across Arizona, and the Arizona Emergency Medical Systems LLC, which coordinates 85 emergency medical services agencies statewide. A Steering Committee comprising local, regional, and national stakeholders provides guidance and oversight for all study activities. To promote rapid learning, two consecutive OBLS implementation and evaluation cycles will be conducted, with the second cycle incorporating feedback and lessons learned from the first. HCWs from 16 implementation sites (8 per cycle) serving areas with high maternal vulnerability indexes will be trained as OBLS instructors. These instructors will train at least 160 HCWs (80 per cycle) within their respective or nearby institutions. Outcomes to be assessed include reach (proportion and representation of institutions offering OBLS, instructors trained, and HCWs participating), effectiveness (impact of OBLS on knowledge and clinical competencies, presence of code carts containing OBLS cognitive aids and resuscitative cesarean delivery kits in hospitals, and the use of an OB Arrest Alert in prehospital settings), adoption (allocation of resources for OBLS), implementation (number of courses completed, fidelity of the training delivery), and maintenance (extent to which training becomes integrated into routine practice and policy). Discussion Findings from this statewide study will be used to promote the scale-up and sustainability of OBLS, ultimately enhancing maternal healthcare quality and equity.